Signaling pathways in cutaneous wound healing - Krizanova, Olga; Penesova, Adela; Sokol, Jozef; Hokynkova, Alica; Samadian, Amir; Babula, Petr (Frontiers in Physiology, 2022)
Wound healing is a very complex process, where variety of different pathways is activated, depending on the phase of healing. Improper or interrupted healing might result in development of chronic wounds. Therefore, novel approaches based on detailed knowledge of signalling pathways that are activated during wound healing enables quicker and more effective healing. In this review we focus on compounds/biomolecules that besides other effects can modulate immune system. Special interest is given to gasotransmitters, as bioactive signalling molecules that can freely diffuse into the cell and exert antioxidative effects. Calcium and vitamin D are important boosters of immune system and they can significantly contribute to healing process. Special interest is given to chronic wounds caused by diabetes mellitus and overcoming problems with the inflammation.